2014
DOI: 10.1111/eth.12211
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Metric of the Attractiveness of Bird Song to Humans

Abstract: The prevalence of passerines (mostly oscines, or songbirds) in international bird trade suggests that the possession or production of a song that is attractive or desirable to people may contribute to the likelihood of a species being traded. Testing this is difficult because we lack a general and readily available metric that quantifies attractiveness of bird song to humans. We propose and validate such a metric, based on the number of sound files lodged for a species on the Xeno‐Canto website (http://www.xen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Two metrics were calculated from these data: 1) the percentage of the body surface covered by each colour, calculated over the fourteen body parts of the bird scored; and 2) colour diversity, calculated as the number of different colours on a given species (excluding colours covering <3% of the body). Song attractiveness: We used the number of song tracks lodged for a given species on the Xeno-Canto website [ www.xeno-canto.org ] to derive a metric of the attractiveness of bird song to humans (following [ 53 ]). Xeno-Canto contains more than 115,000 independent recordings of bird songs, which cover about 80–85% of the extant species, with up to 335 recordings per species.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two metrics were calculated from these data: 1) the percentage of the body surface covered by each colour, calculated over the fourteen body parts of the bird scored; and 2) colour diversity, calculated as the number of different colours on a given species (excluding colours covering <3% of the body). Song attractiveness: We used the number of song tracks lodged for a given species on the Xeno-Canto website [ www.xeno-canto.org ] to derive a metric of the attractiveness of bird song to humans (following [ 53 ]). Xeno-Canto contains more than 115,000 independent recordings of bird songs, which cover about 80–85% of the extant species, with up to 335 recordings per species.…”
Section: Methodsmentioning
confidence: 99%
“…We used the glm function in R v.3.0.3 [ 54 ] to model the log+1 number of songs lodged on Xeno-Canto as a function of log geographic range size. It has been shown that larger residuals are correlated with the characteristics of songs associated with attractiveness to people [ 53 ]. Of the nine predictor variables in the univariate analysis (see below), bird numbers, species status, region of origin, IUCN list and CITES listing, body mass and each colour, breeding range size and the attractiveness of bird song are available for 217 species.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the field recordings from Liaohe Delta Nature Reserve and others deposited on the online sound library Xeno-Canto, we found that vocal activity of female cuckoos peaked in morning rather than in the afternoon. We admit that the call recordings in Xeno-Canto are influenced by human activities (Blackburn et al, 2014) e.g. observers are more likely to spend more time recording birds in good weather and in the morning, which may lead to bias in the interpretation of daily vocal behavior patterns.…”
Section: Temporal Patterns Of Female Vocal Activitymentioning
confidence: 99%